Vitamin D Status in Central Europe - Pawel Pludowski; William B. Grant; Harjit Pal Bhattoa; Milan Bayer; Vladyslav Povoroznyuk; Ema Rudenka; Heorhi Ramanau; Szabolcs Varbiro; Alena Rudenka; Elzbieta Karczmarewicz; Roman Lorenc; Justyna Czech-Kowalska; et al. (International Journal of Endocrinology)
Little published information is available regarding epidemiological data on vitamin D status in the large geographical region of Central Europe (CE). We searched the journal literature with regard to 25(OH)D concentrations among community-dwelling or healthy people living in CE. 25(OH)D concentrations varied by age, season, study sample size, and methodological approach [i.e., 25(OH)D assay used]. Concentrations of 25(OH)D in CE appeared lower than 30 ng/mL, and the magnitude of hypovitaminosis D was similar to that reported in Western Europe. While most of the studies reviewed were cross-sectional studies, a longitudinal study was also included to obtain information on seasonal variability. The longitudinal study reported wintertime 25(OH)D values close to 21–23 ng/mL for all studied age groups, with a significant increase of 25(OH)D in August reaching 42 ng/mL for those aged 0–9 years, but only 21 ng/mL for the elderly aged 80–89 years. The decrease in 25(OH)D with respect to age was attributed to decreased time spent in the sun and decreased vitamin D production efficiency. Based on the literature review on vitamin D status in the CE populations, it can be concluded that 25(OH)vitamin D levels are on average below the 30 ng/mL level.